PENGARUH PEMUPUKAN NPK DAN BAHAN ORGANIK PADA ABSORSI P, PERTUMBUHAN DAN HASIL KEDELAI DI PSAMMENTS BANTUL - Abdul Syukur; Nisrina Nisrina; Sulakhudin Sulakhudin (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2008)
Effect of NPK Fertilizer and Organic Matter on P Absorption, Growth and Yield of Soybean in Psamments Bantul. The research aimed to study combination of NPK fertilizer, and manure on P absorption, growth, and yield of soybean in Psamments Bantul. The research was done in green house, Soil Physical and Chemical Laboratory, Department of Soil, Agricultural Faculty, Gadjah Mada University Yogyakarta from February to May 2007. The factorial completely randomized design with 2 factors and 3 replications used in the research with the first factor was dosage of cow manure (O) with 3 levels: O0 (0 ton/ha), O1 (20 ton/ha), and O2 (30 ton/ha). The second factor was dose of NPK fertilizer (A) with 5 levels: A0 (0 kg/ha), A1 (75 kg/ha), A2 (150 kg/ha), A3 (225 kg/ha), A4 (300 kg/ha). They were separated into two parts, forty five polybags were observed until maximal vegetative and the others were observed on harvesting to observe amount of seed per plant and seed dry weight per plant. Data analyzed using Analysis of Variance with 5% significance of level and followed with Duncan`s Multiple Range Test (DMRT). The results indicated that interaction between NPK fertilizer and manure effected significantly on P content of shoot, P absorption of shoot and root wet weight with best dose combination of 300 kg/ha of NPK fertilizer and 30 ton/ha manure. Concentration of P in 300 kg/ha NPK equivalent to 35.25 kg/ha of SP‐36 can’t increased plant growth and yield of soybean due to the dose is lower than dose of SP‐36 fertilizer that generally used by farmer. Keywords: NPK fertilizer, organic matter, soybean, psamments